APPLICATION OF THE DEAF SPACE CONCEPT IN THE DESIGN OF SPECIAL SCHOOL FOR THE DEAF (SLB-B) - Permadi, Rully; Anggriani, Niniek; Winarto, Erwin Djuni (Border: Jurnal Arsitektur, 2019)
Special school for the deaf (SLB-B) in West Surabaya is a special education facility for deaf people in East Java which aims to develop deaf people to become independent and ready for global competition. The school was specially designed according to the characteristics and behaviors of deaf people who have limitations in receiving verbal information (sounds), due to disability in their hearing senses from birth or birth defects, so that the deaf is more likely to rely on the sense of sight to be able to receive information. However, now we live in a world that relies on delivering information through voice media. Therefore, there needs to be a place where the deaf is able to adapt to the environment more and gain education before they are finally ready in the real global competition. Based on these issues, this study aims to design an educational building specifically designed for the deaf (deaf space), with the theme "see the world, face the future" which can be interpreted that education is one of the most important things in human life, education can open knowledge and knowledge to the greatest extent so that with good education people will be more prepared to face global competition in the future.